The Influence of the Fine Earth Composition of the Soil Mixture on the Parameters of Its Filtration, Moisture Content, and Density - Bekbasarov, Isabai; Suienshbayeva, Kuralay; Atenov, Yerlan; Shanshabayev, Nurzhan (Salehan Institute of Higher Education, 2025)
The article presents the results of laboratory studies on the patterns of change in the filtration coefficient of the fine-grained component (fine earth) of the soil mixture from a number of influencing factors. The study was conducted to assess the impact of the fine earth fractional composition of a soil mixture on its filtration parameters and density-moisture state. The experiments were conducted using a compression device, the use of which is regulated by the standard of the Republic of Kazakhstan. One hundred and twenty-six fine earth samples were tested, containing 50 to 75% (by weight) of various fractions with particle sizes smaller than 5 mm. An analysis of the test results revealed that for large fractions (with particle sizes of 5 mm or less, but more than 1 mm), the filtration coefficient of fine earth increases as the weight content of fractions in it increases (from 50 to 75%), while for small fractions (with particle sizes of 1 mm or less), it decreases. It was determined that similar patterns are characteristic of the increase in moisture content and increase in the density of fine earth, which occur when water is filtered through it. The scientific novelty of the research lies in the fact that, based on the identified patterns, correlation dependencies were established between the filtration coefficient and the weight content of various fractions, as well as the increase in moisture content and the increase in the density of fine earth. Correlation dependencies of the filtration coefficient on the weight content of various fractions, as well as on the increase in moisture content and increase in the density of fine earth, were established. Based on the established relationships, formulas were developed for predicting the filtration coefficient, moisture content, and density of fine earth, which adds practical value to the research. These formulas are recommended for use in selecting optimal fine earth compositions for soil mixtures used in dam construction.